Interpretative Phenomenological Analysis of the Lived Experiences of Older Adults Regarding Their Functional Activities in Ghana. (June 2020) - Awuviry-Newton, Kofi; Tavener, Meredith; Wales, Kylie; Byles, Julie
Introduction: Research on disability largely draws on epidemiological data, often conducted in more developed countries. To date, there is little research related to older adults in Ghana, Africa. The purpose of this study was to strengthen understanding of how older adults in Ghana perform functional activities, referenced against the World Health Organization's International Classification of Functioning, Disability and Health (WHO-ICF) framework.Methods: Interpretative phenomenological analysis (IPA) of semistructured interview data was employed as the methodological approach. Using purposive criterion sampling, 8 older adults admitted to Komfo Anokye Teaching Hospital in Ghana, presenting with any identified health condition and/or frailty were recruited.Results: Analysis of interview data identified 5 interrelated themes: (1) feeling anxious, (2) feeling restricted, (3) understanding and admitting difficulty, (4) striving to be healthy and being productive, and (5) managing functional difficulty. These concerns were classified and related to the WHO-ICF, particularly the contextual factors.Discussion: This study examined in detail experiences of older adults performing functional activities. Our study highlights the relevance of the WHO-ICF framework for understanding the health needs of older adults, emphasizing the functional, social, and environmental factors influencing the functional status of older adults. The findings offer unique insight into the health needs of older adults, drawing attention to the implications for policy and care.